EXTRA appearance - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
'EXTRA'' appearance 'EXTRA', a review of development and extension matters, is a publication in Portuguese which appeared for the first time in May 1989. It will now come out quarterly. For more details, contact: Revista EXTRA Centro de Formaco...